The Impact of Community Trust and Participation on Village Fund Utilization and Rural Economic Development: A Case Study of Padang Matinggi Village, Padang Lawas Regency - Serly Charita Harahap; Purnama Ramadani Silalahi; Waizul Qarni (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the effects of community trust and community participation on Village Fund utilization and rural economic development in Padang Matinggi Village, Padang Lawas Regency. A quantitative survey method was applied to 96 respondents using purposive sampling and analyzed with multiple linear regression (SPSS). The results show that community trust has a positive and significant effect on Village Funds Utilization (t = 13.749; sig. < 0.05) and village economic improvement (t = 3.734; sig. < 0.05), community participation has a positive and significant effect on Village Funds Utilization (t = 12.154; sig. < 0.05) and village economic improvement (t = 3.272; sig. < 0.05), and Village Fund utilization has a positive and significant effect on village economic improvement (t = 2.873; sig. = 0.005 < 0.05). Community trust and community participation simultaneously explain 73.9% of the variation in Village Fund utilization, while all three variables simultaneously explain 41.5% of the variation in village economic improvement (F = 21.749; sig. < 0.05), with the remaining 58.5% influenced by other factors outside this study. Therefore, strengthening community trust and participation is essential to optimizing Village Fund management for sustainable village economic growth.